Agreement between heart rate at first ventilatory threshold on treadmill and at 6-min walk test in coronary artery disease patients on β-blockers treatment - Calegari L. (2021)
© 2021. Korean Society of Exercise Rehabilitation.The purpose of this study was to verify the accuracy of the agreement between heart rate at the first ventilatory threshold (HRVT1) and heart rate at the end of the 6-min walk test (HR6MWT) in coronary artery disease (CAD) patients on β-blockers treatment. This was a cross-sectional study with stable CAD patients, which performed a cardiopulmonary exercise test (CPET) on a treadmill and a 6-min walk test (6MWT) on nonconsecutive days. The accuracy of agreement between HRVT1 and HR6MWT was evaluated by Bland–Altman analysis and Lin’s concordance correlation coefficient (rc), mean absolute percentage error (MAPE), and standard error of estimate (SEE). Seventeen stable CAD patients on β-blockers treatment (male, 64.7%; age, 61 ±10 years) were included in data analysis. The Bland–Altman analysis revealed a negative bias of −0.41 ±6.4 bpm (95% limits of agreements, −13 to 12.2 bpm) between HRVT1 and HR6MWT. There was acceptable agreement between HRVT1 and HR6MWT (rc=0.84; 95% confidence interval, 0.63 to 0.93; study power analysis=0.79). The MAPE of the HR6MWT was 5.1% and SEE was 6.6 bpm. The ratio HRVT1/HRpeak and HR6MWT/HRpeak from CPET were not significantly different (81% ± 5% vs. 81 % ±6%, P =0.85); respectively. There was a high correlation between HRVT1 and HR6MWT (r =0.85, P<0.0001). Finally, the results of the present study demonstrate that there was an acceptable agreement between HRVT1 and HR6MWT in CAD patients on β-blockers treatment and suggest that HR66MWT may be useful to prescribe and control aerobic exercise intensity in cardiac rehabilitation programs.